Participation in dance training in Finland : a study of motives and behavior regulation - Thesleff, Paula (2014)
According to the self-determination theory (Deci & Ryan, 1985; 2000), motivation mediates the relationship between physical activity participation and well-being. In environments such as classical ballet that are highly controlling and competitive, intrinsic motives towards training and self-determined forms of behavior regulation are especially important. Therefore, the purpose of the current study was to examine the various participation motives and behavior regulations of dance students. A secondary aim was to investigate group differences across age, competitive level and dance form. Altogether 103 dance students from three schools across Southern Finland completed the Physical Activity and Leisure Motivation Scale (PALMS; Morris & Rogers, 2004) and the Behavior Regulations in Sport Questionnaire (BRSQ; Lonsdale, Hodge & Rose, 2008). After initial data screening, the Cronbach’s alphas were calculated to check the internal consistencies of the subscales of the measurements, and Pearson correlation coefficient was analyzed to examine the inter-subscale correlations. Overall, the results revealed that dance students participate in dance for motives related to enjoyment, mastery and psychological condition, and that they are intrinsically motivated to participate. An independent-samples t-test was used to examine the group differences across age, and revealed significant differences: older dance students scored lower in PALMS mastery and competition/ego and higher in BRSQ amotivation than their younger counterparts. An ANOVA was used to investigate the group differences across competitive level but yielded no significant differences between any groups. An independent samples t-test revealed significant differences in participation motivation between dancers from different dance forms: ballet dancers’ participation motives were more related to competition/ego and less to enjoyment and psychological condition, and they scored higher in introjected behavior regulation compared to dancers from other dance forms. According to the tenets of the self-determination theory (Deci & Ryan, 2000), the findings of the study implicate that overall, the participation motivation of dance students facilitates optimal adaptation to training in the competitive setting of dance. However, in order to avoid drop-out with age, and facilitate dancers’ well-being in the long run, a task-involving and autonomy-supportive environment is relevant, especially in such dance settings like ballet where requirements are extreme.